The Factor Analysis of Organizational Commitment, Job Satisfaction, and Performance Among Lecturers in Batam - Hazriyanto, Hazriyanto; Ibrahim, & Badaruddin (Journal of Technical Education and Training, 2019)
This article intended to determine the important elements in commitment, satisfaction and job performance of among lecturers in universities. This study involved 179 respondents from 3 universities located in Batam, Indonesia. The population is sampled in this study. The survey instrument had used a 5-point Likert scale to obtain feedback. Overall, the survey had achieved a very high level of reliability for organizational commitment, job satisfaction, and job performance. The data obtained was processed using exploratory factor analysis (EFA) to examine the structure of the commitment, satisfaction, and performance factors. Overall the instruments are valid. Instrument used was a questionnaire. It was found, based on the EFA, that the three important factors were commitment, satisfaction, and performance. Hence, how could the findings significantly solve the problem statements, state the vision and potential of future studies. The Rotated Component Matrix showed the correlation between items and the factors after the Varimax rotation. Factor 1 contained 13 items, Factor 2 contained 12 items, while Factor 3 contained 11 items. It was found that items in Factor 1 could be under the â€œCommitment Factorâ€, items in Factor 2 could be under the â€œPerformance Factorâ€, while items under factor 3 could be under the â€œSatisfaction Factorâ€. The outcome of this study could act as a guideline for lecturers to excel in their careers as well as assist institutions to develop effective evaluations.